Interaction of Fusarium oxysporum with Meloidogyne incognita on Roselle - K. H. Ooi; B. Salleh; M. H. Hafiza; A. A.A. Zainal; M. Said (Universitas Gadjah Mada, 1999)
Forty isolates of Fusarium oxysporum were tested for their pathogenicity to roselle (Hibiscus sabdariffa L. var. sabdariffa) in a plant house. The most virulent isolate was later used in a disease complex experiment with a root-knot nematode Meloidogyne incognita. Disease severity of roselle seedlings inoculated with a combination of fungus and nematode was higher than those inoculated with either fungus or nematode individually. Seedlings that were inoculated with fungus two weeks after nematode inoculation showed the highest disease severity compared to that inoculated with nematode two weeks after fungal inoculation or that inoculated simultaneously with both pathogens. It seems that root infections by M. incognita increased the colonization of roselle by F. oxysporum and subsequently caused higher damage to the roselle seedlings. The high wilt incidence in the presence of M. incognita and F. oxysporum may be due to the synergistic relationship between these two pathogens.